Factors affecting pain relief in response to physical exercise interventions among healthcare workers. (28th December 2016) - Jakobsen, M. D.; Sundstrup, E.; Brandt, M.; Andersen, L. L.
Abstract : The aim of this study is to identify factors associated with musculo‐skeletal pain reduction during workplace‐based or home‐based physical exercise interventions among healthcare workers. Two hundred female healthcare workers (age: 42.0, BMI: 24.1, average pain intensity: 3.1 on a scale of 0‐10) from three hospitals participated. Participants were randomly allocated at the cluster level (18 departments) to 10 weeks of (i) workplace physical exercise (WORK) performed in groups during working hours for 5 × 10 minutes per week and up to five group‐based coaching sessions on motivation for regular physical exercise, or (ii) home‐based physical exercise (HOME) performed alone during leisure‐time for 5 × 10 minutes per week. Linear mixed models accounting for cluster identified factors affecting pain reduction. On average 2.2 (SD: 1.1) and 1.0 (SD: 1.2) training sessions were performed per week in WORK and HOME, respectively. The multi‐adjusted analysis showed a significant effect on pain reduction of both training adherence ( P =.04) and intervention group ( P =.04) with participants in WORK experiencing greater reductions compared with HOME. Obesity at baseline was associated with better outcome. Leisure‐time exercise, daily patient transfer, age, and chronic pain did not affect the changes in pain. In conclusion, even when adjusted for training adherence, performing physical exercise at the workplace is more effective than home‐based exercise in reducing musculo‐skeletal pain in healthcare workers. Noteworthy, obese individuals may especially benefit from physical exercise interventions targeting musculo‐skeletal pain.